Digitalization of Creative Markets: Efforts to Develop Family Economic Resilience in Lampung - Siti Zulaikha; Enny Puji Lestari; Titut Sudiono; Maulana Husen S (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
This study aims to analyze the digitalization of the creative market on the economic growth of the family and to see the role of the family in the economic resilience of the community. This research uses a qualitative method with a case study approach that is field research. Sources of data from creative markets in two districts, namely Metro City and East Lampung. The results of the study indicate that the creative market is able to encourage family economic growth towards a more established direction, and build family relationships in economic resilience. The digitalization of the creative market has also been proven to be able to improve the family’s economy, such as meeting secondary and tertiary needs, education savings and retirement savings, fulfilling education costs, and fulfilling kitchen utensils. Another indication of the progress of the family economy is also marked by the development of fundamental aspects that support the creative economy, such as creativity, innovation, and invention. These three aspects can then affect creative business opportunities that are more wide open, more diverse livelihoods, easier to f ind additional income, souvenirs typical of tourist areas, and the title of a tourist city